Critical Assessment of the Concepts and Misconceptions of the Cardiac Conduction System over the Last 100 Years: The Personal Quest of Robert H. Anderson - Eduardo Back Sternick; Damián Sánchez-Quintana (Journal of Cardiovascular Development and Disease, 2021)
Anatomical concepts regarding the conduction system of the heart have been a matter of debate since pioneering work done at the beginning of the 20th century. Robert H. Anderson was actively involved in this field for half a century. We aimed to investigate how his own concepts evolved over time. We have assessed anatomical concepts relating to the cardiac conduction system appearing since the key contributions made in the initial decade of the 20th century, analyzing them from the perspective of Robert H. Anderson, particularly focusing on the anatomical aspects of structures such as accessory atrioventricular pathways, including the so-called Mahaim-type fibers, connections between the atrioventricular node and the atrial myocardium, and so-called “specialized” internodal atrial tracts. To accomplish this task, we have taken as our starting point the initial concepts published in the first decade of the century, along with those subsequently reported up to 1976, and assessing them in the light of our most recently published works. The concepts put forward by Robert Anderson with regard to atrioventricular nodal bypass tracts, atrioventricular nodal inputs, decrementally conducting accessory pathways, and “tracts” for internodal atrial conduction, have remained consistent along the time frame of half a century.